A Numerical Study on Chain-Die Forming of the aluminium profiles with variable cross-section. Issue 1 (June 2021) - Lu, K; Liang, Z; Liu, Y; Zou, T; Li, D; Ding, S
Abstract: Roll forming is a widely used forming process of profile with constant cross-section because of its high quality, high efficiency, and low cost. However, variable cross-section profiles are becoming more common with the development of the vehicle industry while the demand can't be met by the traditional roll forming technique. Chain-die forming is a newly introduced technique to deal with the problem. Chain-die forming extends the deformation zone by enlarging the rotation radii of the moulds. The study focused on the finite element simulations of chain-die forming aluminium profiles with variable cross-section and the comparation with high strength steels. The results showed the influence of materials such as anisotropy on wrinkling and scratch in chain-die forming and verify the finite element simulation in predicting the chain-die forming results.